Evaluation of diarrhea in Iranian children under five years of age - Jafary Nia, N; Arjmand Kermani, N; Dezfulian, A; Hossein- Khan, N; Noori- Nayer, B; Derakhshan, F; Jafary, F; Lofdahi, S; Zali, M,R (Advances in Nursing & Midwifery, 2007)
Abstract Background: Diarrhea is still one of the leading causes of death among children. Purpose: The descriptive study was conducted to evaluate epidemiologic and clinical factors in diarrheal children under five living in Tehran from April 2005 for one year. Methods: Totally 617 subjects including 551 (89%) children with acute diarrhea and 66 (11%) with chronic diarrhea were enrolled in the study. Results: Watery elimination was the most common manifestation of diarrhea (62.5% of subjects). The highest frequency of watery and bloody diarrhea was detected in autumn and of mucoid diarrhea in winter. Nausea, vomiting and fever were significantly higher at watery form of diarrhea (P= 0.0001, P=0.0001, and P= 0.03 respectively) but there was no correlation between these symptoms and mucoid or bloody form of diarrhea. Significant increase of anorexia was detected during the autumn, mainly at the ages of 5, 1.5 and 2 respectively (P=0.001). Fever and dehydration were significantly higher in those with more severe diarrhea over 1 day (P= 0.03 and P= 0.0001 respectively). Conclusion: Although many new findings about clinical characteristics of community-acquired diarrhea among young children in Tehran were revealed, our lack of understanding regarding the etiology of most episodes in this common pediatric disease was evident. Further studies to assess other environmental determinants, feeding patterns, immunization status of children and gastrointestinal pathogens in pediatric diarrhea are also recommended. Key words: Diarrhea, Child, Incidence.